2018
DOI: 10.3390/w10060773
|View full text |Cite
|
Sign up to set email alerts
|

Improved Assessment of Energy Recovery Potential in Water Supply Systems with High Demand Variation

Abstract: Enhancing energy efficiency of water supply systems by recovering part of the excessive pressure is currently an issue of growing interest for water companies. The installation of micro hydro plants for energy recovery can be profitable in sites with excessive pressure, though requiring proper technical and economical evaluation. This paper presents a methodology for assessing the energy recovery potential in water supply systems under high seasonal demand variation. The methodology is based on the calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For example, the flow rate ranges 25 to 30 m 3 /h and 30 to 35 m 3 /h have nearly the same frequency, but the latter range has a substantially greater expected annual energy generation. Some other authors have used long-term average values in their turbine design methods [15,25]. It is worth noting that average hourly or average daily flow data can be misleading, since the inflow rate might be much higher than the hourly average but occurring only periodically for only short periods of time (e.g., for 5 min at a time, with 15 min in between times of active flow).…”
Section: Comparison Of Results Using the Newly Proposed Methods With Omentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the flow rate ranges 25 to 30 m 3 /h and 30 to 35 m 3 /h have nearly the same frequency, but the latter range has a substantially greater expected annual energy generation. Some other authors have used long-term average values in their turbine design methods [15,25]. It is worth noting that average hourly or average daily flow data can be misleading, since the inflow rate might be much higher than the hourly average but occurring only periodically for only short periods of time (e.g., for 5 min at a time, with 15 min in between times of active flow).…”
Section: Comparison Of Results Using the Newly Proposed Methods With Omentioning
confidence: 99%
“…The tool assumes the selection of a single turbine with a narrow acceptable operating range, and considers neither the possibility of turbines with wide operating ranges nor that of multiple turbines, the latter of which might lead to greater energy generation [25,27]. This was decided partly for simplicity's sake and partly out of the belief that a single turbine generally represents the most economically viable solution for class 1 sites, which is supported by one of the studies cited above [25].…”
Section: Limitations Of the Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have contributed to studies of RRHS from different perspectives. Monteiro, based on an estimation of the turbine performance, maximized the energy production by giving the available head and flow rate values over one year for a specific energy recovery technology [17]. Alnaimi demonstrated that the stability of RRHS can be guaranteed by force analysis to help select durable material under pressure.…”
Section: Introductionmentioning
confidence: 99%